A Brief History of Use of Animals in Biomedical Research and Perspective on Non-Animal Alternatives. (25th June 2021) - Kinter, Lewis B; DeHaven, Ron; Johnson, David K; DeGeorge, Joseph J
Abstract: Animals have been closely observed by humans for at least 17 000 years to gain critical knowledge for human and later animal survival. Routine scientific observations of animals as human surrogates began in the late 19th century driven by increases in new compounds resulting from synthetic chemistry and requiring characterization for potential therapeutic utility and safety. Statistics collected by the United States Department of Agriculture's Animal and Plant Health Inspection Service and United Kingdom Home Office show that animal usage in biomedical research and teaching activities peaked after the mid-20th century and thereafter fell precipitously until the early 21st century, when annual increases (in the UK) were again observed, this time driven by expansion of genetically modified animal technologies. The statistics also show a dramatic transfer of research burden in the 20th and 21st centuries away from traditional larger and more publicly sensitive species (dogs, cats, non-human primates, etc) towards smaller, less publicly sensitive mice, rats, and fish. These data show that new technology can produce multi-faceted outcomes to reduce and/or to increase annual animal usage and to redistribute species burden in biomedical research. From these data, it is estimated that annual total vertebrate animal usage in biomedical research and teaching in the United States was 15 to 25 million per year during 2001–2018. Finally, whereas identification and incorporation of non-animal alternatives are products of, but not an integral component of, the animal research cycle, they replace further use of animals for specific research and product development purposes and create their own scientific research cycles, but are not necessarily a substitute for animals or humans for discovery, acquisition, and application of new (eg, previously unknown and/or unsuspected) knowledge critical to further advance human and veterinary medicine and global species survival.